2015
DOI: 10.1080/03066150.2015.1046447
|View full text |Cite
|
Sign up to set email alerts
|

Understanding rural resistance: contemporary mobilization in the Brazilian countryside

Abstract: Contradictions between impressive levels of economic growth and the persistence of poverty and inequality are perhaps nowhere more evident than in rural Brazil. While Brazil might appear to be an example of the potential harmony between large-scale, export-oriented agribusiness and small-scale family farming, high levels of rural resistance contradict this vision. In this introductory paper, we synthesize the literature on agrarian resistance in Brazil and situate recent struggles in Brazil within the Latin Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…To mitigate the risks imparted by visibility, acts of overt resistance are often combined with networking tactics (e.g., connections with NGOs, alliances between regional organizations, etc. ), which not only provide financial, political, and legal support (Bush, 2011; McDaniel, 2002; Pahnke et al, 2015) but also, critically, serve to hinder the repression of resistance through the bearing of witness (Joshi, 2020; van der Heiden, 2021). Alternatively, people may employ stealthier tactics of opposition, which afford greater protection through the maintenance of anonymity (Borras & Franco, 2013; Hall et al, 2015).…”
Section: Strategies To Hold On To Controlmentioning
confidence: 99%
“…To mitigate the risks imparted by visibility, acts of overt resistance are often combined with networking tactics (e.g., connections with NGOs, alliances between regional organizations, etc. ), which not only provide financial, political, and legal support (Bush, 2011; McDaniel, 2002; Pahnke et al, 2015) but also, critically, serve to hinder the repression of resistance through the bearing of witness (Joshi, 2020; van der Heiden, 2021). Alternatively, people may employ stealthier tactics of opposition, which afford greater protection through the maintenance of anonymity (Borras & Franco, 2013; Hall et al, 2015).…”
Section: Strategies To Hold On To Controlmentioning
confidence: 99%
“…Throughout the 2000s, Brazil was hailed as a laboratory for new forms of local and transnational governance through innovations like participatory budgeting, popular councils ( conselhos ), and international mobilizations inspired by spaces like the World Social Forum (see Gohn, 2015 for a review). A large literature showed that indigenous peoples (Bicalho, 2010), informal workers (Rosaldo, 2018), women (Costa, 2013), black movements (Paschel, 2016a), quilombolas (Leite, 2008), peasants (Pahnke et al, 2015; Tarlau, 2019), queer movements (Facchini, 2009), and people at the intersection of these groups conquered state power and political subjecthood in the post-democratization period (Paschel, 2016b). This body of scholarship carefully documented the improbable gains of these movements.…”
Section: Literature Review: Brazilian Civil Society In the 21st Centurymentioning
confidence: 99%
“…These debates are echoed in peasant studies. Pahnke, Tarlau, andWolford (2015: 1074) consider that the emphasis of political process theories on rationality "complicates the explanation of intra-movement processes." These concepts shed light on less visible aspects of collective action.…”
Section: Political Change and State-society Relations In Latin Americamentioning
confidence: 99%